Superbodies : between freedom and subjugation - Pang, Natalie (2011)
In a time where technology practically develops itself, it is up to us to define and re-define our bodies. When technology successfully melds with biology, cyborgs exist – not only as fictitious beings, but also within our own reality as well. Undoubtedly, the cyborg conjures up various fantastic images in the minds – they can be human-like and organic like the replicants in Blade Runner, or they can be mechanical like in Ghost in the Shell. However, Donna Haraway argues that the cyborg is not merely a simple “hybrid of machine and organism” (149), but a “kind of disassembled and resembled, postmodern collective and personal self” (163). Also more importantly, it also introduces a post-human, post-gendered idea of a cyborg that liberates the woman who is chained to identity politics. The Harawayan cyborg is at the same time, a promise for and a threat to the liberation of the woman. This essay will aim to show how the body can be liberated and yet at the same time still be bound by patriarchy, using the cyborg and the human in Mamoru Oshii’s Gōsuto In Za Sheru (1995, Ghost in the Shell) and Ryu Murakami’s Ōdishon (1999, Audition) respectively.